El comportamiento informativo de los investigadores en geografía: el Instituto de Geografía de la UNAM - Calva González, Juan José; Santos Rosas, Antonia (Revista General de Información y Documentación, 2009)
Research about information seeking behaviour of researches in geography in the National Autonomous University of Mexico, in specific in Institute of Geography. Survey was applied at researchers in the Intitute. The variable category was research versus resources that researchers of Institute use for satisface his information need. The test applied was Pearson “C”.
Keywords: Information behaviour; Information needs; Geographies; Researchers